2021
DOI: 10.1186/s13104-021-05768-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological spectrum of Diffuse Large B Cell lymphoma: a study targeting population yet unexplored in Pakistan

Abstract: Objective Diffuse Large B Cell Lymphoma (DLBCL) is the most common type of Non-Hodgkin Lymphoma (NHL). The aim of this study was to assess the clinico pathological characteristics of DLBCL specifically, among the affected individuals residing in Northern areas of Pakistan who had not been previously included in major lymphoma studies due to their remote location. Results Mean age of the patients was 49.7 years. Male: female ratio was 1.5:1. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Jayanta et al found that the GIT is the most common extranodal site for NHL involvement, based on a retrospective analysis of pictorial positron emission tomography (PET) scans from different regions [18]. Our study showed similar results to those reported in other studies [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Jayanta et al found that the GIT is the most common extranodal site for NHL involvement, based on a retrospective analysis of pictorial positron emission tomography (PET) scans from different regions [18]. Our study showed similar results to those reported in other studies [13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 87%
“…The mean age of all NHL patients in a study by Shahid et al [ 13 ] was 46.31+18 years. According to Mahmood et al, the mean age of the patients was 49.7 years [ 14 ]. Our results are similar to those of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are different regional registries in Pakistan, but no central registry is available [11]. Given the increase in lymphoma cases and the scarcity of data in this regard, a comprehensive study about the lymphoma burden in Pakistan is an urgent necessity.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) is the most prevalent subtype of non-Hodgkin lymphoma (NHL), accounting for about 30% to 40% of the whole NHL. [ 1 ] As a highly heterogeneous malignant tumor, DLBCL has great differences in tumor biological characteristics, clinical manifestations, treatment response and prognosis. [ 2 ] About one-third of DLBCL patients are initially refractory or relapse after first-line chemotherapy.…”
Section: Introductionmentioning
confidence: 99%